2020
DOI: 10.1016/j.jagp.2020.06.024
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Benefits of Physical Activity in Older Adults Survive the COVID-19 Pandemic

Abstract: Highlights This survey collected information about depression, anxiety, and physical activity levels of 1,046 older adults living in North America under current social distancing guidelines during the COVID-19 pandemic. The primary question addressed by the study was whether total physical activity levels and physical activity intensities performed by older adults during COVID-19-related SDG was related to mental health symptoms. The results of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
190
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(243 citation statements)
references
References 35 publications
16
190
0
12
Order By: Relevance
“…Four studies had a prospective longitudinal design [26,29,39,36], one was a cross-sectional study with a retrospective measure of the exposure factor (henceforth treated as retrospective) [5], and 16 were crosssectional studies [9, 23-25, 27, 29-35, 37, 6, 38, 40, 28, 41]. A total of 7 studies were conducted in Asia [24,25,27,30,33,39,40], 6 in Europe [9,26,31,32,35,36], 3 in South America [28,29,6], 3 in North America [23,34,5], one in Oceania [38] and one study included a multinational sample [37].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies had a prospective longitudinal design [26,29,39,36], one was a cross-sectional study with a retrospective measure of the exposure factor (henceforth treated as retrospective) [5], and 16 were crosssectional studies [9, 23-25, 27, 29-35, 37, 6, 38, 40, 28, 41]. A total of 7 studies were conducted in Asia [24,25,27,30,33,39,40], 6 in Europe [9,26,31,32,35,36], 3 in South America [28,29,6], 3 in North America [23,34,5], one in Oceania [38] and one study included a multinational sample [37].…”
Section: Resultsmentioning
confidence: 99%
“…Results are summarized and presented in table 2. Out of 9 studies reporting analyses on the association between the overall volume of PA and depression, 6 studies showed that more PA is signi cantly associated with less depression symptoms [23,25,32,33,35,37], and 3 out of 8 studies investigating the association between the overall volume of PA and anxiety symptoms showed that more PA is signi cantly associated with less anxiety symptoms [25,32,35]. 3 out of 5 studies reported higher frequencies of PA to be signi cantly associated with less depression [27,29,36] and 2 out of 4 studies to be signi cantly associated with less anxiety [27,29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the most important finding of the present study was that it was the VPA intensity which better predicted depressive symptoms, which is consistent with previous research 21 and with a very recent study that has assessed depression, anxiety and PA levels in North America under current social distancing guidelines during the COVID-19 pandemic. 25 Callow et al 25 found that LPA and VPA levels were independent contributors towards depression symptoms in older adults. These results are consistent with the findings of this study, except for the nonsignificant association of LPA with depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the literature reviewed during the COVID-19 pandemic suggests that PA is linked to individuals’ mental health. 25 , 26 , 27 However, to date, the associations between resilience, affect, depressive symptoms, and PA during the quarantine in the elder population is unknown. Hence, it seems important to understand how the preventive measures against the outbreak of the COVID-19 may affect psychological well-being of older people that are home isolated during the ongoing pandemic.…”
Section: Introductionmentioning
confidence: 99%